Measurement programs in software development determinants of success. - Gopal, A. (IEEE Transactions on software engineering)
Measurement programs in software organizations are an important source of control over quality and cost in software development. The findings of this research presented here are based on an industry-wide survey conducted to examine the factors that influence success in software metrics programs. Our approach is to go beyond the anecdotal information on metrics programs that exists in the literature and use the industry-wide survey data to rigorously test for the effects of various factors that affect metrics programs success. We measure success in metrics programs using two variables-use of metrics information in decision-making and improved organizational performance. The various determinants of metrics program success are divided into two sets-organizational variables and technical variables. The influence of these variables on metrics programs success is tested using regression analysis. Our results support some of the factors discussed in the anecdotal literature such as management support, goal alignment, and communication and feedback. Certain other factors such as metrics quality and the ease of data collection are not as strongly influential on success. We conclude the paper with a detailed discussion of our results and suggestions for future work.